The Role of Modified Mediterranean Diet and Quantum Therapy in Type Diabetes Mellitus Primary Prevention - Stagnaro, Sergio; Caramel, Simone (Journal of Pharmacy and Nutrition Sciences, 2013)
The Authors provide an overview of useful treatments such as ‘Modified Mediterranean Diet’, CoQ10, melatonin, carnitine and ‘Quantum Therapy’, testing their effects in Type 2 Diabetes Mellitus (T2DM) primary prevention, performed possibly in the three first stages of T2DM. This is done through ‘Quantum Biophysical Semeiotics’ biological evaluation, clinically monitoring the results and efficiency of ongoing therapies aimed at improving mitochondrial and endothelial function, when it is impaired in any biological systems. This clinical method allows physicians to bedside assess tissue acidosis, before and during different preventive therapies, testing their respective efficacy and utility. All the investigated treatments have firstly ameliorated and then normalized tissue microcirculatory pattern, showing a physiological functioning. Furthermore the tested ‘Quantum therapy’ generates virtuous genetic feedbacks. ‘Quantum Biophysical Semeiotics’ theory is an extension of medical semeiotics. It is grounded on a multidisciplinary approach that involves chemistry and biology, genetics and neuroscience, chaos theory and quantum physics.It is based on the method of ‘Auscultatory Percussion’, through which by means of the common stethoscope, it is possible to listen to the signs that the body gives us when appropriately stimulated.The stimuli are used to induce consistent behavior in precise and welldefined biological systems of the human body, thus giving local qualitative information on the state of health or disease, whether potential, being developed but not yet evident by usual clinical trial, effective or even in chronic phase. The 'Quantum Biophysical Semeiotics’ theory provides very detailed case studies based on the latency time, duration, and intensity of the reflexes, which play a central role in such a diagnostic method.